Physiotherapists’ reliability of inter-recti distance measurement with real-time ultrasound across a mixed women population sample - Evdokia Billis; Anastasia Skoura; Tatiana-Elena Papakonstantinou; Dimitra Tania Papanikolaou; Maria Tsekoura; Maria Andriopoulou; Charalampos Matzaroglou; Sofia Lampropoulou; Dimitra Koumoundourou; Eftichia Trachani; Theofani Bania; Elena Drakonaki (Women's Health)
Background: Ultrasound imaging has become popular among physiotherapists for monitoring diastasis rectus abdominis postpartum, but its reliability requires further exploration. Objectives: To investigate physiotherapists’ intra-tester, inter-tester, and test-retest reliability of inter-recti distance measurement utilizing real-time ultrasound across a mixed women sample. Design: Reliability study. Methods: Volunteers comprising nulliparous and parous women of different ages and body mass index participated. Five physiotherapists performed ultrasound measurements, following sonographic training. Four conditions were tested in supine; rest, curl-up, transversus abdominus activation, and transversus abdominus with curl-up. Three locations were randomly measured: umbilicus, 3 cm above the umbilicus, and halfway between the umbilicus and xiphoid process. For intra-tester reliability, each therapist undertook three repeated measurements. For inter-tester reliability, mean inter-recti distance measurements were explored across any two tester combinations within and across sessions. Test-retest reliability explored repeated measurements 5–8 days later. Data were analyzed with intraclass correlation coefficients 2,1 . Results: 54 women (33.2 ± 15.2 years old, body mass index: 24.2 ± 3.7), 19 (35.2%) being parous participated. Intra-tester reliability across each physiotherapist was very good (intraclass correlation coefficients = 0.677–0.989). Intra-session reliability across any two testers yielded very good results (intraclass correlation coefficients = 0.76–0.92), whereas across-session yielded good reliability (intraclass correlation coefficients >0.76) except for one condition (3 cm above umbilicus in combined transversus abdominus and curl-up). Test-retest reliability was also very good (intraclass correlation coefficients = 0.78–0.96). Significant differences in inter-recti distance were found, with parous women showing consistently larger values (p < 0.05). Conclusion: Physiotherapists, following sonographic training, can reliably measure inter-recti distances in both nulliparous and parous women across active and resting tasks. Thus, ultrasound measurement of inter-recti distance is recommended in physiotherapy practice for monitoring diastasis rectus abdominis and assessing rehabilitation progress. However, sub-umbilical inter-recti distance measurements and the impact of co-contraction on reliability require further research.